Tailored mobile text messaging interventions targeting type 2 diabetes self-management: A systematic review and a meta-analysis. (April 2019) - Sahin, Cigdem; Courtney, Karen L; Naylor, PJ; E Rhodes, Ryan
Objectives: This study aimed to identify, assess and summarize available scientiﬁc evidence on tailored text messaging interventions focused on type 2 diabetes self-management. The systematic review concentrated on message design and delivery features, and tailoring strategies. The meta-analysis assessed the moderators of the effectiveness of tailored text messaging interventions. Methods: A comprehensive search strategy included major electronic databases, key journal searches and reference list searching for related studies. PRISMA and Cochrane Collaboration's guidelines and recommended tools for data extraction, quality appraisal and data analysis were followed. Data were extracted on participant characteristics (age, gender, ethnicity), and interventional and methodological characteristics (study design, study setting, study length, choice of modality, comparison group, message type, format, content, use of interactivity, message frequency, message timing, message delivery, tailoring strategies and theory use). Outcome measures included diet, physical activity, medication adherence and glycated hemoglobin data (HbA1C). Where possible, a random effects meta-analysis was performed to pool data on the effectiveness of the tailored text messaging interventions and moderator variables. Results: The search returned 13 eligible trials for the systematic review and 11 eligible trials for the meta-analysis. The majority of the studies were randomized controlled trials, conducted in high-income settings, used multi-modalities, and mostly delivered informative, educational messages through an automated message delivery system. Tailored text messaging interventions produced a substantial effect ( g = 0.54, 95% CI = 0.08–0.99, p < 0.001) on HbA1C values for a total of 949 patients. Subgroup analyses revealed the importance of some moderators such as message delivery ( Q B = 18.72, df = 1, p = 0.001), message direction ( Q B = 5.26, df = 1, p = 0.022), message frequency ( Q B = 18.72, df = 1, p = 0.000) and using multi-modalities ( Q B = 6.18, df = 1, p = 0.013). Conclusions: Tailored mobile text messaging interventions can improve glycemic control in type 2 diabetes patients. However, more rigorous interventions with larger samples and longer follow-ups are required to confirm these findings and explore the effects of tailored text messaging on other self-management outcomes.